Evidence, theory and context: using intervention mapping in the development of a community-based self-management program for chronic low back pain in a rural African primary care setting - the good back program - Chinonso N. Igwesi-Chidobe; Sheila Kitchen; Isaac O. Sorinola; Emma L. Godfrey (BMC, 2020)
Abstract Background Rural Nigeria has one of the greatest burdens of low back pain but there are no effective evidence-based interventions to manage it in this population. This paper presents the application of the intervention mapping (IM) approach in the development of a complex behavior change intervention - The Good Back program, aimed at reducing non-specific chronic low back pain (CLBP) disability in rural Nigeria. Methods The first four steps of IM were applied. A critical review of the literature, 2 qualitative studies and a population-based cross-sectional study in rural Nigeria helped to identify two key program objectives in order to reduce CLBP disability in this population: reduce the impact of illness perceptions, fear avoidance beliefs, catastrophising, anxiety and depression by targeting maladaptive illness perceptions about CLBP; and facilitate the adoption of exercises and good posture to limit disability. A systematic review plus these studies, identified the personal and environmental determinants of the performance objectives including health literacy, self-awareness, self-efficacy, personal preference, health professional skills, health facility structure and family/community support. The theory, techniques and strategies for modifying personal and environmental determinants were also identified from these studies. Intervention components and materials were then produced for practical application. The initial developed intervention was described. Results The feasibility and acceptability of the developed program was then tested using a small pragmatic non-randomised controlled study incorporating qualitative exit feedback interviews in a rural Nigerian primary health care centre. The program appeared feasible and acceptable when delivered by a highly trained physiotherapist. There were promising clinical outcomes in disability, pain intensity, illness perceptions, fear avoidance beliefs and pain medication use. Suggestions for program improvement included shorter but ongoing sessions, video demonstration of exercises/good posture, spacious exercise/demonstration rooms, and community legitimisation of exercise as treatment for back pain. Subsequent modifications to program content and delivery were then described. Theoretical modification included the addition of aspects of the social cognitive theory to the Leventhal's self-regulatory model of illness cognitions. Conclusions IM appears to be a suitable framework for designing complex behavior change interventions in rural Nigeria. The need for further testing of the intervention was highlighted.